2006
DOI: 10.1101/gad.381806
|View full text |Cite
|
Sign up to set email alerts
|

The Zinc-finger factor Insm1 (IA-1) is essential for the development of pancreatic β cells and intestinal endocrine cells

Abstract: The pancreatic and intestinal primordia contain epithelial progenitor cells that generate many cell types. During development, specific programs of gene expression restrict the developmental potential of such progenitors and promote their differentiation. The Insm1 (insulinoma-associated 1, IA-1) gene encodes a Zinc-finger factor that was discovered in an insulinoma cDNA library. We show that pancreatic and intestinal endocrine cells express Insm1 and require Insm1 for their development. In the pancreas of Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
217
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(234 citation statements)
references
References 55 publications
16
217
1
Order By: Relevance
“…Such deficiencies are also observed in Insulinoma-associated antigen 1 (Insm1), Regulatory X-box binding 6 (Rfx6), and Islet1 (Isl1) mutants. Loss of Insm1 or Rfx6 arrests the differentiation of endocrine precursors towards hormone-expressing cells (Gierl et al, 2006;Mellitzer et al, 2006;Soyer et al, 2010;Smith et al, 2010). A phenotype similar to Rfx6 mutant mice has also been reported in human infants carrying mutation in the Rfx6 gene, who have an autosomal recessive syndrome of neonatal diabetes, Mitchell-Riley syndrome (Smith et al, 2010).…”
Section: Class I: General Endocrine Precursor Differentiation Factorsmentioning
confidence: 81%
“…Such deficiencies are also observed in Insulinoma-associated antigen 1 (Insm1), Regulatory X-box binding 6 (Rfx6), and Islet1 (Isl1) mutants. Loss of Insm1 or Rfx6 arrests the differentiation of endocrine precursors towards hormone-expressing cells (Gierl et al, 2006;Mellitzer et al, 2006;Soyer et al, 2010;Smith et al, 2010). A phenotype similar to Rfx6 mutant mice has also been reported in human infants carrying mutation in the Rfx6 gene, who have an autosomal recessive syndrome of neonatal diabetes, Mitchell-Riley syndrome (Smith et al, 2010).…”
Section: Class I: General Endocrine Precursor Differentiation Factorsmentioning
confidence: 81%
“…The INSM1 transcription factor has emerged as an important regulator for pancreatic endocrine cell differentiation (4,5). Extensive biochemical studies have revealed the DNA consensus binding sequence, transcriptional repressor activity, downstream target genes, upstream regulatory protein of INSM1, and its restricted expression pattern (1-3, 9, 14, 15).…”
Section: Discussionmentioning
confidence: 99%
“…A predicted binding site for MyT1, a known pancreatic transcription factor (50), was identified within the fp3 region. Putative binding sites for IA1 and HNF4, two additional well characterized pancreatic regulatory factors (51)(52)(53), are coincident with the fp4 region, as were possible binding sites for two generally expressed regulatory factors, Sp1 and GABP. The fp5 region also contained a second Sp1 site.…”
Section: Dna Footprint Analysis Of the Proximal Site 2-and Site 3-conmentioning
confidence: 99%